2019
DOI: 10.1080/00207543.2019.1574040
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal collaborative transport: survey of solutions and practical implementation issues

Abstract: Horizontal collaboration has been considered as effective practice for sustainable logistics and freight transport and it has gained increased attention in recent years. This paper aims to provide a survey of the development of horizontal collaborative transport (HCT) over the past ten years, to identify research trends and gaps, then to propose some research opportunities. The paper also aims to provide guidelines to logistics companies who wish to embark on HCT, to help them choose which HCT solution to impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(123 citation statements)
references
References 139 publications
(164 reference statements)
2
119
0
2
Order By: Relevance
“…While the literature on vertical collaboration point to size similarity as an important element ensuring a balance of power in the relationship, HLC requires also the partners to have similar products and processes. The results from the case studies presented in Chapter 3 show the role played by partners similarity in the partners' selection process, which is in line with the recent literature on HLC (Pan et al, 2019). This observation is further confirmed by the consistent significant impact of partners' processes and products similarity on joint relationship efforts across industry and country categories.…”
Section: 41: Contribution To the Literature On Horizontal Logisticsupporting
confidence: 82%
See 1 more Smart Citation
“…While the literature on vertical collaboration point to size similarity as an important element ensuring a balance of power in the relationship, HLC requires also the partners to have similar products and processes. The results from the case studies presented in Chapter 3 show the role played by partners similarity in the partners' selection process, which is in line with the recent literature on HLC (Pan et al, 2019). This observation is further confirmed by the consistent significant impact of partners' processes and products similarity on joint relationship efforts across industry and country categories.…”
Section: 41: Contribution To the Literature On Horizontal Logisticsupporting
confidence: 82%
“…Festus and Xiaoming (2010) work showed a direct positive impact of information sharing on collaboration on reverse logistics activities. Panahifar et al (2018) also showed that information sharing has a direct positive impact on collaboration effectiveness, and subsequently the firm's performance. In comparing buyers and suppliers' opinions regarding supply chain collaboration antecedent, Nyaga et al (2010) showed that information sharing had a direct positive impact on trust and commitment, which in turn have a positive impact on the collaboration outcomes.…”
Section: Information Sharingmentioning
confidence: 92%
“…In the FSLP, however, collaboration is at the sequence level. This type of collaboration, which [34] refer to as 'co-joint routing and which is most allied to 'logistics pooling' in the fine-grained classification offered by [37], has the most potential for significant reductions in cost and emissions, but requires a suitably configured and capable planning algorithm to hand. Research has explored this form of opportunistic collaboration in a variety of contexts; some studies focus on specific sectors (e.g., airport ground operations [38], coastal port operations [39] and grocery retailers [40], while others investigate this in the context of generic road freight [17,28,41].…”
Section: Ict To Support Sequence-level Collaboration In Freight Logismentioning
confidence: 99%
“…In our literature review we bring together two streams of research, which are the one on operations pooling and on distributed decision-making. Various collaborative planning schemes have been introduced in the literature (Fransoo, Wouters, and de Kok 2001;Taghipour and Frayret 2013;Thomas et al 2015;Gansterer and Hartl 2018b;Pan et al 2019). These are referred to as horizontal, if participants act at the same levels in a market (Cruijssen, Dullaert, and Fleuren 2007).…”
Section: Literature Reviewmentioning
confidence: 99%